2009
DOI: 10.1190/1.3215771
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging of complex onshore structures by 2D elastic frequency-domain full-waveform inversion

Abstract: Quantitative imaging of the elastic properties of the subsurface at depth is essential for civil engineering applications and oil- and gas-reservoir characterization. A realistic synthetic example provides for an assessment of the potential and limits of 2D elastic full-waveform inversion (FWI) of wide-aperture seismic data for recovering high-resolution P- and S-wave velocity models of complex onshore structures. FWI of land data is challenging because of the increased nonlinearity introduced by free-surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
292
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 539 publications
(304 citation statements)
references
References 58 publications
1
292
0
3
Order By: Relevance
“…Initial applications of FWI were performed in the time domain, but were limited given the high computational demand of the method (Kolb et al 1986). Three decades later and FWI is still performed based on these underlying principles, with modern codes capable of performing FWI in either the time or frequency domain, in two or three dimensions, approximating either the acoustic or elastic wave equation, and can include the effects of seismic attenuation and anisotropy (e.g., Pratt 1999; Brossier et al 2009;Warner et al 2013). It has also been shown that the maximum achievable resolution using these codes is on the order of half the seismic wavelength, making it superior to travel-time tomography .…”
Section: Full Waveform Inversionmentioning
confidence: 99%
“…Initial applications of FWI were performed in the time domain, but were limited given the high computational demand of the method (Kolb et al 1986). Three decades later and FWI is still performed based on these underlying principles, with modern codes capable of performing FWI in either the time or frequency domain, in two or three dimensions, approximating either the acoustic or elastic wave equation, and can include the effects of seismic attenuation and anisotropy (e.g., Pratt 1999; Brossier et al 2009;Warner et al 2013). It has also been shown that the maximum achievable resolution using these codes is on the order of half the seismic wavelength, making it superior to travel-time tomography .…”
Section: Full Waveform Inversionmentioning
confidence: 99%
“…To enhance the signal-to-noise ratio, FWI often uses several bands of frequencies (Brossier et al, 2009) in a multi-scale approach (Bunks et al, 1995). The common approach in frequency-domain FWI is stacking multiple misfit functionals for single frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…This guides FWI to a local minima of the objective function and prevents further model improvements, especially in deep explorations. Gradual offset increase (Brossier et al, 2009) or various misfit functions (Choi and Alkhalifah, 2015, e.g. ) can help mitigate the problem in the data domain.…”
Section: Introductionmentioning
confidence: 99%
“…Many choices of E functionals exist, L 2 being the most common choice. However, some other norms have been successfully applied to the FWI problem, such as the L 1 norm [7,8,45,48], the Huber norm [19] or separating phase and envelope misfits in the time-frequency domain [16,24]. In this study, we employ the normalized least square criterion L 2 given by…”
Section: Theorymentioning
confidence: 99%
“…Additional mathematical insights such as preconditioning and regularization also play an important role in reducing the non-linearity of the problem and are often required in order to ensure convergence [3,12,20]. On the other hand, FWI becomes very challenging as at least two parametres must be determined either independently or using constrains, and hence, the parametre space becomes larger and more complex [7,8,46].…”
Section: Introductionmentioning
confidence: 99%